Understanding sources of social desirability bias in different modes: Evidence from eye-tracking - Olena Kaminska; Tom Foulsham (University of Essex, Institute for Social and Economic Research (ISER), 2013)
Our paper provides an empirical study of whether satisficing is related to social desirability bias using real-world eye-tracking. The method enables detecting latency of eye gazes in web, face-to-face and paper and pencil self-administered (SAQ) modes. Through these we infer respondents' attention to question wording, socially desirable and socially undesirable response scale points. We link the gaze latency measures to responses to understand how respondents arrive at socially desirable or undesirable answers. We find that satisficing is related to social desirability bias in self-completion modes. Yet it does not explain the higher incidence of socially desirable responses in face-to-face mode.
Keywords: C81; C83; 330; social desirability; mode effect; satisficing; eye-tracking; GHQ-12